2020
DOI: 10.1002/ange.202011770
|View full text |Cite
|
Sign up to set email alerts
|

σ‐Conjugation and H‐Bond‐Directed Supramolecular Self‐Assembly: Key Features for Efficient Long‐Lived Room Temperature Phosphorescent Organic Molecular Crystals

Abstract: Long‐lived room temperature phosphorescence from organic molecular crystals attracts great attention. Persistent luminescence depends on the electronic properties of the molecular components, mainly π‐conjugated donor–acceptor (D‐A) chromophores, and their molecular packing. Here, a strategy is developed by designing two isomeric molecular phosphors incorporating and combining a bridge for σ‐conjugation between the D and A units and a structure‐directing unit for H‐bond‐directed supramolecular self‐assembly. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Because the sample absorbance was the same at 360 nm (Figure S7), the difference in p RTP brightness and endurance occurred only because of the large difference in Φ p (RT) and τ p (RT). In Figure d, to the best of our knowledge, we have shown that the reported chromophores had a Φ p (RT) ≥ 20% with τ p (RT) ≥ 0.1 s. , This example fulfills the given criteria, even though a combination of Φ p (RT) ≥ 20% with τ p (RT) ≥ 1.0 s shortens the window. In this work, we have shown that the chromophores have a τ p (RT) greater than 2 s with a Φ p (RT) of 35%, which is at the highest level for Φ p (RT) and τ p (RT).…”
Section: Resultsmentioning
confidence: 62%
“…Because the sample absorbance was the same at 360 nm (Figure S7), the difference in p RTP brightness and endurance occurred only because of the large difference in Φ p (RT) and τ p (RT). In Figure d, to the best of our knowledge, we have shown that the reported chromophores had a Φ p (RT) ≥ 20% with τ p (RT) ≥ 0.1 s. , This example fulfills the given criteria, even though a combination of Φ p (RT) ≥ 20% with τ p (RT) ≥ 1.0 s shortens the window. In this work, we have shown that the chromophores have a τ p (RT) greater than 2 s with a Φ p (RT) of 35%, which is at the highest level for Φ p (RT) and τ p (RT).…”
Section: Resultsmentioning
confidence: 62%
“…In other words, we believe that our present work shows that future quantum chemical-based investigations of ISC in solid states should include several molecules in their model to more accurately investigate the origin of the ISC rather than basing their conclusion on individual molecules. 14,55 Furthermore, our work highlights the necessity to see the SOC as a dynamical phenomenon sensitive to transient as well as permanent molecular distortion. These distortions can be managed by molecular engineering based on a new theory of the SOC/ molecular conformation relationship as rich as all what was done in the chromophore photophysics such as the J/H aggregates theory.…”
Section: ■ Conclusionmentioning
confidence: 88%
“…12 T h i s c o n t e n t i s Among those, it has been established that introducing a permanent distortion of the π-system of a conjugated molecule (i.e., a minimum on the potential energy surface, PES) or a dynamical one (i.e., temperature-induced motion) can result in a large SOC between the S 1 and T 1 states. 2,6,13,14 A more recent approach consists in building dimers to mix the individual electronic states of monomers. 2,15−18 It has been suggested in most of these works that the dimerization favors the ISC process through a delocalization of the electronic transition over the two elementary subunits of the dimer molecule, leading to a change in the nature of the transition from a local (LE) to a charge-transfer (CT) type of excited state.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Distinguished from traditional chemistry which was erected by covalent interactions, supramolecular chemistry gives prominence on reversible and noncovalent interactions encompassing p-p interactions, hydrogen bonding, electrostatic effects, host guest interactions, etc. 14 Supramolecular self-assembly of p-conjugated chromophores [15][16][17] mediated by hydrogen bonding 18 yields an electrifying opportunity to exploit the multidirectional nature of the classic non-covalent interaction, which are the emerging class of materials that have applications in wide range of elds. 19 This explicitly denes the structural framework of photo-physically abundant building blocks in the self-assembled state, which oen leads to hierarchical arrangements with divergent luminescent properties 20 and transport properties, 21,22 especially if the building blocks are semiconductor in nature.…”
Section: Introductionmentioning
confidence: 99%